2022
DOI: 10.3390/molecules27238329
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant, Anti-Bacterial, and Anti-Cancer Activities of Essential Oils Extracted from Citrus limetta Risso Peel Waste Remains after Commercial Use

Abstract: Citrus plants are widely utilized for edible purposes and medicinal utility throughout the world. However, because of the higher abundance of the antimicrobial compound D-Limonene, the peel waste cannot be disposed of by biogas production. Therefore, after the extraction of D-Limonene from the peel wastes, it can be easily disposed of. The D-Limonene rich essential oil from the Citrus limetta risso (CLEO) was extracted and evaluated its radical quenching, bactericidal, and cytotoxic properties. The radical que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Neem has been reported to exhibit antibacterial activity against a wide range of bacterial strains. 37 On the other hand, the antibacterial activity of A3 can be attributed to the presence of bioactive compounds such as citral, hesperidin, and limonene 38 and a rich essential oil such as D-limonene 39 present in sweet lemon extract. These compounds have been reported to exhibit antibacterial activities against a wide range of bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
“…Neem has been reported to exhibit antibacterial activity against a wide range of bacterial strains. 37 On the other hand, the antibacterial activity of A3 can be attributed to the presence of bioactive compounds such as citral, hesperidin, and limonene 38 and a rich essential oil such as D-limonene 39 present in sweet lemon extract. These compounds have been reported to exhibit antibacterial activities against a wide range of bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51] The other two main substances found in different essential oils are cisterpinene, and α-myrcene, both of which have been demonstrated to possess strong antibacterial, anti-inflammatory, and anticancer effects. [52,53] The study observed significant radical quenching properties against DPPH, ABTS and hydrogen peroxide radicals. The 2,2'azinobis-(3-ethylbenzothiazoline-6-sulphonate) radical (ABTS +) and 1,1-diphenyl-2-picrylhydrazyl (DPPH•) are synthetic organic radicals which are used to represent the activity of antioxidant molecules.…”
Section: Discussionmentioning
confidence: 96%
“…Apart from that, significant antiproliferative activity against cancer cells and murine tumor models have also been reported for D‐Limonene; the prominent mechanism of anticancer potential is reported to be apoptosis and autophagy‐mediated death [49–51] . The other two main substances found in different essential oils are cis‐terpinene, and α‐myrcene, both of which have been demonstrated to possess strong antibacterial, anti‐inflammatory, and anticancer effects [52,53] …”
Section: Discussionmentioning
confidence: 99%
“…Essential oils are natural mixtures produced by plant metabolism that are less persistent and biodegradable and have been used successfully against phytophagous insects. The essential oil extraction from crop residues also helps in effective agricultural waste management ( Kuttithodi et al, 2023 , Narayanankutty et al, 2022 ). The development, growth, and adult emergence of insects are significantly influenced by essential oils ( Dey and Gupta, 2016 ).…”
Section: Introductionmentioning
confidence: 99%